2012
DOI: 10.1289/ehp.1104307
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A Concentrations and Implantation Failure among Women Undergoing in Vitro Fertilization

Abstract: Background: Bisphenol A (BPA) is a synthetic chemical widely used in the production of polycarbonate plastic and epoxy resins found in numerous consumer products. In experimental animals, BPA increases embryo implantation failure and reduces litter size.Objective: We evaluated the association of urinary BPA concentrations with implantation failure among women undergoing in vitro fertilization (IVF).Methods: We used online solid phase extraction–high performance liquid chromatography–isotope dilution tandem mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(105 citation statements)
references
References 42 publications
2
99
1
Order By: Relevance
“…In animal studies, BPA exposure has led to a significant reduction in embryo implantation (379). Exposure to BPA is believed to lead to a downregulation of HOXA10 expression (217), with IVF embryo implantation failure being more common in women with higher urinary BPA levels (93). A United States study of women with unexplained miscarriage demonstrated that those with a serum conjugated BPA concentration in the highest quartile were almost twice as likely to miscarry as those women in the lowest quartile.…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…In animal studies, BPA exposure has led to a significant reduction in embryo implantation (379). Exposure to BPA is believed to lead to a downregulation of HOXA10 expression (217), with IVF embryo implantation failure being more common in women with higher urinary BPA levels (93). A United States study of women with unexplained miscarriage demonstrated that those with a serum conjugated BPA concentration in the highest quartile were almost twice as likely to miscarry as those women in the lowest quartile.…”
Section: Endocrine Disrupting Chemicalsmentioning
confidence: 99%
“…Several prospective IVF cohort studies examined associations between BPA and early IVF outcomes in women. [218][219][220][221][222] Significant negative associations between BPA and peak ovarian estradiol were observed in multiple cohorts, although other associations were only observed in a single cohort (i.e., oocyte yield, and other downstream IVF outcomes). In one cohort, later reproductive endpoints (i.e., embryo implantation) were negatively associated with urinary BPA concentrations.…”
Section: -53mentioning
confidence: 99%
“…BPA and its metabolites are widely distributed in humans and animals (Calafat et al, 2005;Melzer et al, 2010), and were detected in more than 90% of urine samples from the U.S. population in the 2003-2004 and 2005-2006 National Health and Nutrition Examination Survey (Calafat et al, 2008;Lakind and Naiman, 2011). As a known endocrine disruptor, BPA has been shown to interfere with hormonal and homeostatic systems, and BPA levels in human urine have been correlated with various diseases and adverse health outcomes (Braun et al, 2011;Carwile and Michels, 2011;Ehrlich et al, 2012;Lang et al, 2008;Lassen et al, 2014). BPA exposure has also been associated with reproductive dysfunctions, including reduction of testicular weight and sperm count, alterations of hormone levels, and impairment of spermatogenesis (Jin et al, 2013;Pacchierotti et al, 2008;Sakaue et al, 2001;Tiwari and Vanage, 2013;Wang et al, 2016).…”
mentioning
confidence: 99%